Analysis of Nanomedicine Efficacy for Osteoarthritis. Issue 12 (20th November 2022) - Wang, Yuwen; Liu, Ling; Le, Zhicheng; Tay, Andy
Abstract : Osteoarthritis (OA) is a chronic disease and it causes considerable medical and socioeconomic burden. Currently, OA can be classified into different stages depending on its severity, from mild to severe, but there is no treatment focusing on a particular stage. In addition, conventional treatments suffer from drawbacks such as the poor effectiveness of physiotherapy, short‐term efficacy of medication, and invasiveness of surgery. Nanomedicine is a promising approach to improve OA treatments such as by prolonging the residence time of drugs in the joint and on‐demand drug release. Herein, the pathological development of OA and the cellular involvement in this process is reviewed and classified into three stages: early, intermediate, and advanced, according to its pathology and severity. Subsequently, nanomaterials that have been used to deliver drug cargo relevant to different stages of OA are reviewed. The impact of nanomaterial physicochemical properties, on therapeutic efficacy, is discussed. This is concluded by discussing the significance of minimum information reporting to standardize the use of nanomedicine for OA treatment and the potential of emerging methods including microneedles and DNA barcoding technology to improve the understanding of OA biology and improve clinical translation. Abstract : The pathology of osteoarthritis (OA) involves a complex interplay of molecular and cellular events. In particular, tissue resident macrophages play a significant role in OA progression. Nanomaterials can be optimized for their physicochemical properties and coupled with external stimuli for improved drug delivery.